Report: Special Training on Hydrographic Surveying in Canada 4 June -16 September, 1994 - Mahmud, Mohd. Razali (Fakulti Ukur dan Harta Tanah, 1994)
This training was part of Canada Hydrographic Association (CHA) assistance in providing an advanced hydrographic training programme for UTM lecturers at established Canadian University and hydrographic agencies. The financial support for this project was provided by Canadian International Development Agency (CIDA). Two lecturers from the Centre for Hydrographic Studies were chosen for this training namely, Usmuni Din and myself. Overall, we were trained at the University of New Brunswick plus six hydrographic agencies by experienced and skill supervisors. This report will look briefly into the training experienced at all six places and the work they are associated with. The training started in Fredericton at the University of New Brunswick for eight weeks followed by two weeks at Universal System Limited to receive training on the CARIS systems. Next, we went to Vancouver to receive a one day training on the ECDIS systems followed by two weeks field programme on the British Columbia coast with the Canadian Hydrographic Service. Finally, the remaining time were spent at Quester Tangent Corporation to receive training on the ISAH systems, with a short summary and review period at the Institute of Ocean Sciences in Sidney, British Columbia.